26.7k views
4 votes
Simplify the expression (10 + 3i)(10 - 3i).​

User Rezizter
by
4.9k points

2 Answers

7 votes


(a-b)(a+b)=a^2-b^2

Therefore


(10 + 3i)(10 - 3i)=100-9i^2

User Camposer
by
5.2k points
7 votes

Answer:

109

Explanation:


\textbf{Assuming}~ i ~\textbf{as the imaginary unit, where}~ i = √(-1)~ \textbf{and}~ i^2 = -1\\\\\textbf{Given that,}\\\\~~~(10+3i)(10-3i)\\\\=10^2 -(3i)^2~~~~~~~~~~;\textbf{Difference of two squares} ~a^2 -b^2 = (a+b)(a-b)\\\\=100-9i^2\\\\=100-9(-1)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~;{i^2 = -1}\\\\=100+9\\\\=109

User Rodrigo Salvo
by
5.2k points